Study of the Hydrolysis Process Using Bromelain Enzymes on the Characteristics of Hydrolyzed Protein from Jengki Anchovies (Stolephorus indicus) - Yumni , Dalilah Edenya Zata; Rosida, Dedin Finatsiyatull (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Fish protein hydrolysates have great potential in various fields, particularly in food. Researchers developed fish hydrolysates enzymatically to utilize anchovies and produce functional fish-based food products that meet standards. This study aims to find out how different amounts of bromelain enzyme and how long the hydrolysis process lasts affect the chemical properties of anchovy protein hydrolysate. The study employed a complete randomized design (CRD) factorial design with two factors and two replications. The first factor was bromelain enzyme concentration (6%, 7%, 8%). The second factor was hydrolysis time (4 hours, 5 hours, 6 hours). Data were analyzed using Analysis of Variance (ANOVA) at a 5% significance level. If we observed significant interactions between the two treatments, we conducted a post-hoc DMRT test at 5%. The best treatment used 8% enzyme concentration and took 6 hours, leading to a moisture content of 82.91%, ash content of 2.46%, soluble protein content of 8.12%, and fat content of 3.27%. SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 12: Responsible Consumption and Production